(untitled) (CAHIERS MAGELLANES-NS, 2024)
Solanum melongena L a member of Solanaceae is generally cultivated as fruit vegetable in sub-tropical and tropical regions of the world. After being treated with microwave irradiation for duration as 0.0,1.0,2.0,3.0 & 5.0 mins and the source of microwave was 630 w (Panasonic). Solanum melongena L seeds were planted for two generations, M1 and M2. The treated plants were identified as the selected mutants that produced desirable characteristics like plant height, number of fruits, fruit size, and early fruiting, among other things. To filter out the genetic variants at the molecular level, seeds from these mutants were gathered and subjected to M3 generation. According to the results of the current investigation, we found that every line that was screened displayed a different banding pattern when compared to the control plant, which is equal to a genetic variation frequency of 36.06%. The fragments that each primer produced, which varied in size from 100 to 1,500 bp, were amplified using PCR. With an average of six bands per primer, the three tested primers produced 35 scorable bands altogether. The bands were repeatable. Each primer has anywhere from five to nine bands. When comparing the ISSR profiles of the mutants to the control, new bands or the absence of bands were found. ISSR test using primer 2 (ISSR-2) yielded 52 bands total, 5 of which were novel bands. were noted, and there were no 06 bands in the lanes. A total of 25 bands were obtained using the ISSR assay with primer 3 (ISSR-3), of which 9 were new bands and 5 were not visible. The ISSR test using primer 9 (ISSR-9) yielded 57 bands in total, of which 5 were new and 5 were not seen, according to the results.35 of the 134 bands that were assessed, with an average polymorphism percentage of 26.11, were polymorphic. The primer ISSR-9 provided the lowest polymorphism (17.54%), while ISSR-3 displayed the highest polymorphism (56.00%) out of the three. Compared to control plants, the seven mutant lines showed notable differences in the banding pattern.